Cyborg Imaginaries: A Computational Grounded Theory of Online Pioneer Community Discussions on Human Augmentation - Frascaria, Giulia; Jaramillo-Dent, Daniela; Latzer, Michael (AoIR Selected Papers of Internet Research, 2026)
Human Augmentation (HA) technologies, such as Brain-Computer Interfaces (BCIs), neurostimulation devices, and microchip implants, are increasingly discussed in online pioneer communities, where early adopters shape imaginaries of technologically mediated human futures. As part of the broader process of digitalization, HA technologies contribute to the platformization of the human body. While these technologies remain experimental, transhumanists and biohackers engage with them as tools for self-enhancement, body modification, and posthuman evolution. These imaginaries are critical to understanding future adoption, yet remain underexplored in scholarly literature.This study applies computational grounded theory (CGT) to analyze discussions on Reddit, identifying emerging sociotechnical imaginaries of HA technologies. Using BERTopic, a transformer-based topic modeling approach, we extract thematic structures from a dataset of 1,503 posts and 60,327 comments spanning 2008–2025. Using BERTopic, a transformer-based topic modeling approach, we extract thematic structures from a dataset of 1,503 posts and 60,327 comments spanning 2008–2025. The imaginaries are then defined through qualitative analysis and iterative refinement of the model, ensuring deeper contextual grounding. Preliminary findings reveal three key dimensions of cyborg imaginaries: (1) Beliefs, including aspirations such as immortality and concerns over job automation; (2) Practices, particularly cognitive and sensory augmentation; and (3) Technological Advances, with discussions centered on BCIs, neural implants, and cybernetic enhancements.This extended abstract presents initial results, contributing to broader discussions on digitalization, human-technology integration, and cyborgization.